Sharif Munawar: An Anonymous Poet from Hyderabad - Rashid, Abdul Qudus Hassan; Shahani, Shafique Ahmed (sourcecoder, 2023)
Sharif Munawar was one of the positively thinking poets of Hyderabad the poets like Qabil Ajmeri, Aijaz Ehsani, Raees Amrohi, Jon Elia, Muhammad Ali Siddiqi, Hasan Abid, Rashid Mufti, Qamar Arzu, Marghoob Akhtar and Razzaque Tahirani were his freinds and associates, while examining bioghraphical notes written on our local poets unfortunately we find no mention of his. it's been several decades since he left this world if he wero not written about today he would probably remain in anonymity, penning about him is a mere effort of bringing him to the limelight from darkness of anonymity.